Transfigurative Spaces and Tantalizing Recipes in Cocinando con Elisa, El Codex Romanoff and Cocinar hombres - Saborío, Linda (Latin American Theatre Review, 2022)
In this study, a concept of space mapped onto fixed and rigid gender identities based on binary masculine and feminine conventional gender roles is reconceptualized by the female protagonists in three Latin American plays: Lucía Laragione’s Cocinando con Elisa, Estela Leñero’s El Codex Romanoff and Carmen Boullosa’s Cocinar hombres. In the kitchen, a traditionally sanctioned female space, the protagonists of these three theatrical pieces feel empowered to create their own ground rules for gender identity and reimagine alternative gender roles not confined by binary social constructs. Through their creation of what theorist Teresa De Lauretis refers to as a "space-off," the female protagonists are able to enact individuality in a predominantly androcentric system and, in the process, expose a social order structured by exclusivity.